2021
DOI: 10.17159/2520-9868/i85a01
|View full text |Cite
|
Sign up to set email alerts
|

Practical subjects in the vocational curriculum: A critical review of the literature

Abstract: There is a growing number of studies in the field of vocational education and training, but not many focus on the practical subjects that prepare students for transition to workplaces. This critical review of the literature on practical subjects in vocational colleges set out to contribute to debates on the relationship between theory and practice in vocational education through a particular focus on the knowledge forms that are evident in curricular and pedagogical practices in practical subjects. The critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The involvement practically in the intervention programme facilitated the learning of the different skills relevant to the students' trade. This is also evident in literature as it is reported that effective practical training requires authentic learning tasks that addresses key vocational competencies (Winberg & Hollis-Turner, 2021), which was present in the intervention programme. The students' experiential learning from the industrial trainer opened their minds on new relevant knowledge as it relates to skills in EIMT.…”
Section: Development Of New Relevant Trade-related Knowledgementioning
confidence: 77%
See 1 more Smart Citation
“…The involvement practically in the intervention programme facilitated the learning of the different skills relevant to the students' trade. This is also evident in literature as it is reported that effective practical training requires authentic learning tasks that addresses key vocational competencies (Winberg & Hollis-Turner, 2021), which was present in the intervention programme. The students' experiential learning from the industrial trainer opened their minds on new relevant knowledge as it relates to skills in EIMT.…”
Section: Development Of New Relevant Trade-related Knowledgementioning
confidence: 77%
“…Besides, the necessity of industry involvement in the training has been reported in different studies globally. These include exposure to practical-based training (Winberg & Hollis-Turner, 2021), exposure to experiential learning by real-life experimentation and latest technology to produce work ready graduates as well as the latest technology to produce work ready graduates (Pherson-Geyser et al, 2020;Mustafa et al, 2022). Others include exposure to industrial transformation for knowledge enhancement as well as adapt to knowledge and update teaching materials (Adams, 2019) and for practical skills acquisition that are aligned to labour market demand (Nathaniel et al, 2019).…”
Section: Industry Stakeholder and Tvet Institution Collaborationsmentioning
confidence: 99%
“…Children when engaged practically improve their sense of attainment. 36% of teachers agreed e-learning met learner styles whereas 64% were of the view e-learning failed to meet all learner styles of learning since the knowledge base of practical subjects involves conceptual analysis, procedural, contextual, and technical forms of knowledge are connected in activities and practical task (Winberg & Hollis-Turner, 2021) which can be less achieved electronically specifically in deprived areas. Goyal (2012) acknowledged that all learners will not find e-learning suitable for their learning style.…”
Section: Effect Of E-learning On Teaching and Learning Practical Subj...mentioning
confidence: 99%
“…The reason for this is evident in that theories are considerably easier to implement in an online or electronic learning environment than practical instructions (Dube, 2020). To enable progressive competent performances in practical subjects, learner-instructor engagement is of the essence, it supports cumulative knowledge building (Winberg & Hollis-Turner, 2021).…”
Section: Effect Of E-learning On Teaching and Learning Practical Subj...mentioning
confidence: 99%
See 1 more Smart Citation